Bone Marrow Mesenchymal Stem Cell-Derived Extracellular Vesicle Infusion for the Treatment of Respiratory Failure From COVID-19 - Lightner, Amy L.; Sengupta, Vikram; Qian, Sascha; Ransom, John T.; Suzuki, Sam; Park, David J.; Melson, Timothy I.; Williams, Brian P.; Walsh, James J.; Awili, Mustafa (Chest, 2023)
Bone marrow mesenchymal stem cell (BM-MSC)-derived extracellular vesicles (ExoFlo) convey the immunomodulatory and regenerative properties of intact BM-MSCs. This study aimed to determine the safety and efficacy of ExoFlo as treatment for moderate to severe ARDS in patients with severe COVID-19. Do two doses of ExoFlo safely reduce mortality in COVID-19-associated moderate to severe ARDS compared with placebo? A prospective phase 2 multicenter double-anonymized randomized placebo-controlled dosing trial was conducted at five sites across the United States with infusions of placebo, 10 mL of ExoFlo, or 15 mL of ExoFlo on days 1 and 4. Patients (N = 102) with COVID-19-associated moderate to severe ARDS were enrolled and randomized to treatment. Adverse events were documented throughout the study. The primary outcome measure was all-cause 60-day mortality rate. Secondary outcomes included time to death (overall mortality); the incidence of treatment-emergent serious adverse events; proportion of discharged patients at 7, 30, and 60 days; time to hospital discharge; and ventilation-free days. No treatment-related adverse events were reported. Mortality (60-day) in the intention-to-treat population was reduced with 15 mL ExoFlo mixed with 85 mL normal saline (ExoFlo-15) compared with placebo (not significant, χ2, P = .1343). For the post hoc subgroup analyses, 60-day mortality was decreased with ExoFlo-15 compared with placebo (relative risk, 0.385; 95% CI, 0.159-0.931; P = .0340; n = 50). With ExoFlo-15, a relative risk of 0.423 (95% CI, 0.173-1.032; P = .0588; n = 24) was determined for participants aged 18 to 65 years with moderate to severe ARDS. Ventilation-free days improved with ExoFlo-15 (P = .0455; n = 50) for all participants aged 18 to 65 years. The 15 mL dose of ExoFlo was found to be safe in patients with severe or critical COVID-19-associated respiratory failure. In participants aged 18 to 65 years, the risk reduction in 60-day mortality was further improved from subjects of all ages in the intention-to-treat population after two doses of 15 mL of ExoFlo compared with placebo. ClinicalTrials.gov; No.: NCT04493242; URL: www.clinicaltrials.gov. [Display omitted]